Brief report: "Quick and (not so) dirty" assessment of change in autism: Cross-cultural reliability of the developmental disabilities CGAS and the OSU autism CGI - Choque Olsson, N.; Bölte, Sven (Springer New York LLC, 2014)
There are few evaluated economic tools to assess change in autism. This study examined the inter-rater reliability of the Developmental Disabilities Children's Global Assessment Scale (DD-CGAS), and the OSU Autism Clinical Global Impression (OSU Autism CGI) in a European setting. Using these scales, 16 clinicians with multidisciplinary background and varying experience independently rated eight vignettes of autism spectrum disorder for severity and general psychosocial functioning at referral and discharge. Intraclass correlation coefficient (ICCs) for experienced clinicians were .75 for the DD-CGAS and .72 for the OSU Autism CGI. In inexperienced clinicians these ICCs were .58 and .59. Results confirm previous North American studies, and further extents the reliability of the instruments to untrained, less experienced clinicians with different professions.